A test of environmental Kuznets curve (EKC) for carbon emission and potential of renewable energy to reduce green house gases (GHG) in Malaysia - Gill, Abid Rashid; Viswanathan, Kuperan K.; Hassan, Sallahuddin (Springer Netherlands, 2018)
This study investigates the presence of environmental kuznets curve (EKC) for green house gases (GHG) measured by CO2 emission in Malaysia for the period 1970 to 2011. The study also examines the potential of the renewable source of energy to contain GHG. The long-run significant positive coefficient of GDP indicates that the GHG are increasing with economic growth while the insignificant coefficient on GDP square rejects the EKC transition. These results indicate a high GDP level for the EKC turning point for Malaysia. Therefore, it can be stated that only economic growth cannot reverse the environmental degradation in Malaysia. The government should have to come up with some policy measures to achieve CO2 emission reduction targets that Malaysia has pledged to achieve in Paris Submit (2015). The renewable energy production is found to have significant negative effect on CO2 emission. So government should focus on the renewable source of energy production and should frame a special policy for renewable energy production.